GAMBARAN ARSITEKTUR TIDUR PADA PASIEN TUMOR OTAK YANG MENGALAMI GANGGUAN TIDUR - Yesi Astri,* Manfaluthy Hakim,* Tiara Aninditha,*Renindra Ananda Aman,** Astri Budikayanti* (Neurona Majalah Kedokteran Neuro Sains, 2021)
INTRODUCTION SLEEP DISORDER IS COMMONLY FOUND IN BRAIN TUMOR PATIENTS 4246 IT CAN BE DETECTED USING THE PITTSBURG SLEEP QUALITY INDEX PSQI AS A SCREENING TOOL AND CONFIRMED BY ANALYZING THE SLEEP ARCHITECTURE OBTAINED THROUGH A POLYSOMNOGRAPHIC PSG EXAMINATION THE AIM OF THIS STUDY IS TO EVALUATE THE SLEEP ARCHITECTURE IN BRAIN TUMOR PATIENTS WHO EXPERIENCE SLEEP DISORDER